IDENTIFICATION OF TECHNICAL CHARACTERISTICS OF MULTIFUNCTIONAL LAPTOP TABLE PRODUCTS BY PAYING ATTENTION TO CUSTOMER VOICES - Hutapea, Mei Fitri; Noor, Asep Mohamad (Universitas Sahid, 2023)
Products circulating in the market either in the form of goods or services to facilitate the daily life of consumers. A good product is a product that meets the needs and desires of consumers so that it can function optimally. Multifunctional laptop desk products are widely used by students or students to make it easier to do tasks such as writing, typing with a laptop, and so on. A multifunctional laptop table has several functions, namely placing the laptop or doing tasks without using a laptop, and also has several features such as a laptop cooling fan which is useful for keeping the laptop's temperature normal when the laptop is used. The voices of consumers include consumers who want multifunctional laptop desk products to be made in rectangular shape, products made of MDF wood, the size of the product is medium with a size of 60cm x 40cm x 30cm, products are made of strong materials and multifunctional laptop table products that will be made have additional features Cooler, Usb Port, and Drawer.